Upcycling of textile products vs trademark right infringement. Material and cross-border litigation strategies - Antón Juárez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The fashion industry, especially the business based on fast fashion, has been configured around massive production of clothing, footwear and accessories. But not only that, textile production itself generates a significant amount of waste (ad ex., leftover fabrics, pieces of leather, etc.) that are discarded directly. In fact, despite the fact that European standards on waste treatment in Europe are changing (proof of this is Law 7/2022 of April 8, on waste and contaminated soils derivated from the European Directive 2018/851), companies still generate a significant number of waste at time to produ- ce and they also have a lot of leftover stock at the end of each season. Thus, some of the solutions that some experts offer to make the industry increasingly sustainable and circular is for textile companies to manufacture less and reuse more of what is already manufactured. Upcycling is a technique that consists of reusing already used products so that they can have a second life. This reuse, often based on creative techniques, does not pose major legal problems when it is the fashion brand itself that reuses its products or reaches an agreement with another company to collaborate together. The problem arises when a third party uses parts of products protected by a trademark right and, without the owner’s consent, adds them to other products. This legal question that we ask ourselves turns out to be even more interesting when we realize that in most cases these new upcycling creations usually reuse parts of products that feature fashion brands that are well-known worldwide and that belong to the segment of products considered “of luxury brands”. The objective of this paper is threefold, so we are going to analyze: 1) If the up- cycling technique could be contrary to an EU trademark right; 2) Whether upcycling would fit within the concept of European exhaustion of trademark rights and to what extent it could be appropriate to adapt exhaustion to achieve a more sustainable industry; 3) The aspects from a private international perspective should be kept in mind in the event that the trademark owner decides to sue for trademark infringement before European courts.